PEMBELAJARAN BERDIFERENSIASI TERINTEGRASI TPACK MATERI ROTASI DAN REVOLUSI BUMI KELAS VI MI SULLAM TAUFIQ KAJEN - Awalia Anzilni; Aan Fadia Annur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Differences in student learning profiles need to be facilitated through differentiated learning so that learning objectives are achieved well. Integrating technology can also increase students’ interest and enthusiasm for learning. The point of this study is to talk about differentiated learning in terms of planning, TPACK integration, the methods teachers use to use differentiated learning with the TPACK approach, and how it affects students' ability to understand and interest in the material. The method used in this research is descriptive qualitative with data collection techniques in the form of interviews, observation, and documentation. The results obtained from the research were that the planning carried out included designing various learning tools, including carrying out diagnostic tests first. Meanwhile, the integration of TPACK in differentiated learning takes the form of using augmented reality-based flashcards as a medium for learning participants to be able to see objects in 3 dimensions. The differentiated learning strategy used includes content, process, and product differentiation. The impact of TPACK's integrated differentiated learning is that it encourages students to be more active in asking questions and discussing, thereby creating a more collaborative learning environment.